Implementing access and benefit sharing in eight countries - Vernooy, Ronnie; Halewood, Michael; López Noriega, Isabel; Otieno, G.; Lapena, I.; Vodohue, R.; Bessette, Guy (Centre for Learning on Sustainable Agriculture (ILEIA), 2016)
Since 2012, national teams in eight countries in Asia, Africa and Latin America have been identifying options for policy, legal and administrative mechanisms for the implementation of the multilateral system of access and benefit sharing (MLS) for plant genetic resources. This article summarises if and how access and benefit sharing has been strengthened in the eight countries, and to what extent this has benefited family farmers.